2021
DOI: 10.1002/adhm.202001369
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Bone Regeneration by MOF Modified Multifunctional Membranes through Enhancement of Osteogenic and Angiogenic Performance

Abstract: Owing to the insufficient guidance of new bone formation in orthopedic and craniomaxillofacial surgery, construction of a guided bone regeneration membrane to support vascularized bone regeneration remains a challenge. Herein, an electrospun asymmetric double‐layer polycaprolactone/collagen (PCL/Col) membrane modified by metal–organic framework (MOF) crystals is developed. The optimization of the PCL/Col weight ratio (1:1 and 1:1.5) enables the composite membrane with a balanced tensile strength (only fell by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 67 publications
1
38
0
Order By: Relevance
“…The weight loss of scaffolds in SBF was evaluated to study the in vitro degradation ( Figure 4 ). We found that all scaffolds degrade slowly in the first 6 days, which meant that the scaffold could provide effective support and protection for bone in the initial stage of bone defect repair ( Qian et al, 2014 ; Tan et al, 2021 ; Xue et al, 2021 ). Subsequently, the degradation rate of the scaffolds accelerated in all groups.…”
Section: Resultsmentioning
confidence: 92%
“…The weight loss of scaffolds in SBF was evaluated to study the in vitro degradation ( Figure 4 ). We found that all scaffolds degrade slowly in the first 6 days, which meant that the scaffold could provide effective support and protection for bone in the initial stage of bone defect repair ( Qian et al, 2014 ; Tan et al, 2021 ; Xue et al, 2021 ). Subsequently, the degradation rate of the scaffolds accelerated in all groups.…”
Section: Resultsmentioning
confidence: 92%
“…Maxillofacial trauma, tumors, and congenital deformities are common causes of craniofacial bone tissue defects. Craniomaxillofacial bones are crucial to maintaining facial beauty, chewing, swallowing, language and other functions, and craniomaxillofacial bone defects can easily lead to serious psychological problems, causing great physical and mental pain to patients and a great burden to the patient's family 31 . The biggest obstacle to the clinical application of the existing craniofacial bone tissue defect repair materials is that the tissue materials lack good osteoinductive and osteogenic properties, so they cannot obtain sufficient amount of mature new bone in a short period of time 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Craniomaxillofacial bones are crucial to maintaining facial beauty, chewing, swallowing, language and other functions, and craniomaxillofacial bone defects can easily lead to serious psychological problems, causing great physical and mental pain to patients and a great burden to the patient's family. 31 The biggest obstacle to the clinical application of the existing craniofacial bone tissue defect repair materials is that the tissue materials lack good osteoinductive and osteogenic properties, so they cannot obtain sufficient amount of mature new bone in a short period of time. 32 , 33 With the rapid development of molecular biology, regenerative biology, and genetic engineering technology, it is of great significance to combine stem cells, biomaterials, and growth factors to regulate cell regeneration, thereby promoting the repair of defective tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For practical applications, a suitable membrane should possess adequate biocompatibility, mechanical strength, permeability, porosity, osteoinductive properties and osteogenic ability [70] , [71] , [72] . Although there are various methods for membrane fabrication, the electrostatic spinning method is the most widely discussed because of the advantages of the prepared nanofiber membranes which have high porosity and a large surface-to-volume ratio, a structure similar to that of the extracellular matrix, and easily optimizable properties [73] , [74] , [75] , [76] , [77] .
Fig.
…”
Section: Tissue Engineeringmentioning
confidence: 99%